Comprehensive 3R’s method's approaches to mitigate plastic pollution and its indirect role in reduction of greenhouse gas emissions: a review - Muhammad Hammad; Dr. Muhammad Kabir (Journal of Sustainable Environment)
Plastic pollution has become an extreme global issue, destroying ecosystems and human health. This comprehensive review investigates the multifaceted challenges posed by plastic waste, ranging from the low recycling rates and mismanagement. Projections of a stunning 12 billion Mt (million metric tons) of plastic waste by 2050 emphasize the urgent effective involvement. The 3R’s approach, surrounding Reduce, Reuse, and Recycle, appears as a vigorous strategy to hold this crisis. Under the "Reduce" banner, bioplastics are the best sustainable alternatives, offering eco-friendly attributes, reduced reliance on non-renewable energy, and reduced greenhouse gas emissions. Other policy tools like single-use plastic restrictions/bans, excessive packaging regulations, and extended producer responsibility also help to reduce plastic waste accumulation in the environment. Transitioning to the "Reuse" model highlights the extension of plastic lifespans through reusable containers and bags, influences industries to prioritize product redesign for durability, implementation of closed-loop system, and supply chain integrations at the industrial level, and advances sustainable initiatives like plastic banks for effective waste management. The "Recycle" dimension explores mechanical and chemical recycling methods, explaining their respective advantages and drawbacks. Importantly, the review underlines the 3R’s indirect role in reducing greenhouse gas emissions, revealing how strategies like minimizing plastic waste and reusable alternatives contribute to a reduced need for production and landfill space. In conclusion, the 3R’s method emerges as a pivotal and comprehensive strategy to combat plastic pollution, requiring widespread adoption across individual, industrial, and policy domains to ensure a sustainable and healthier future for our planet and its inhabitants.